Review on rubbers in medicine: natural, silicone and polyurethane rubbers. (1st July 2013) - Rahimi, A; Mashak, A
<x xml:space="preserve">Abstract</x> Natural, silicone and polyurethane rubbers are considered as three important biomaterials which have found widespread applications in medical technology. Biocompatibility, biodurability, sterilisability, processibility, as well as mechanical properties, such as flexibility and resilience, are properties that make these kinds of rubbers appropriate candidates for medical applications. Medical devices based on natural rubber, silicone and polyurethane rubbers include cardiac pacemaker leads, mammary prostheses, artificial skin, catheters, denture liners, diaphragms, blood pressure cuff coil, tubes and seals. These types of rubbers are commonly used in controlled drug delivery systems as a carrier for pharmaceutical agents and in the fabrication of other medical devices. These polymers were evaluated for release of hormones (e.g. estradiol and progesterone), metronidazole, nonoxynol-9, etc. In this paper, some recent advances on the development of these polymers in the biomedical field and some reports on the modification and improvement of their properties such as drug release and mechanical properties are reviewed.